Stress in a Crisis Context: Experiences of Portuguese Social Workers in Healthcare During COVID-19 - Ferreira, D. C.; Casquilho-Martins, I. (Perspectives on Stress and Wellness Management in Times of Crisis, 2023)
The emergence of COVID-19 led to a global pandemic framework, decreed in March 2020 by the World Health Organization. This phenomenon led to several changes and restrictions in people's lives, which subsequently questioned many professional practices, namely in social work. This chapter aims to analyze the factors and consequences of stress in the professional activity of social workers, as well as the changes in the health area caused by the pandemic crisis context in Portugal. Social workers' stress levels were affected during the COVID-19 pandemic, while recognizing that there were already present and identified causes of stress before the crisis. Work overload, multiple duties, fatigue, and even a decrease in the quality of professional care were aspects mentioned that need addressing, and since social workers intervene with a vulnerable population in different dimensions, greater attention is required. Therefore, the specificity of stress in social workers is correlated to the responsibility and demands of the professional practice itself.